Avaliação do papel da opsonização na suscetibilidade de macrófagos murinos à infecção pelas diferentes espécies de Leishmania - Polonski, Daniella Cristina Silva (2023)
Leishmaniasis are a set of parasitic diseases caused by a protozoa of the Leishmania genus. Clinical manifestations vary according to the Leishmania species and host immune response. Among of the possible clinical manifestation of leishmaniasis, according to the symptomatology, three stand out: visceral, cutaneous and mucosal leishmaniasis. Macrophages are key cells in the prognosis of Leishmania infection. M1 macrophages stimulate the Th1 response are associated with leishmanicidal activity; the M2 macrophages are activated mainly by Th2 lymphocytes are associated with the growth and survival of the parasites. The M2b subtype regulates the immune response and the inflammatory reaction against intracellular parasites and is related to the humoral response. The present work evaluated the susceptibility of different species of Leishmania: Leishmania (V.) braziliensis, Leishmania (L.) major, Leishmania (L.) infantum and Leishmania (L.) amazonensis to in vitro infections, using macrophages from BALB/c and C57BL/6. Murine macrophages were cultured and infected with promastigotes from different Leishmania species, opsonized or not with anti-leishmania antibody. The infection was evaluated by the promastigotes retrieval method at the points: 3 h, 24 h, 72h and 120h. We found that C57BL/6 macrophages are resistant to infection by L. (V.) braziliensis and L. (L) amazonensis. BALB/c mice show susceptibility to L. (L) infantum. Both C57BL/6 and BALB/c infected with L. (L.) major parasites show susceptibility to the parasite. Both in infections with L. major and L. infatum, it was observed that the association with antibodies is more related to the reproduction of the parasites and survival inside the macrophages than to the killing of parasites We therefore conclude that opsonization with anti-leishmania can modulate the macrophage to a characteristic M2b profile, favoring infection.